Efeitos da auriculoterapia com laser de baixa potência sobre os aspectos físicos e emocionais em pacientes com disfunção temporomandibular: um ensaio clínico randomizado cego - Rodrigues, Manuel da Fonseca (2016)
Temporomandibular disorders (TMD) is a clinical condition characterized by the presence of pain in the temporomandibular articulation (TMA), in the masticatory muscles and orofacial region. Its etiology is multifactorial, it is associated mainly to the occlusal pattern, emotional stress, parafunctional habits among others, and it is more common in women between the third and the fourth decade of life. There are several therapeutic modalities for TMD pain relief: pharmacotherapy, the Michigan myorelaxing plaque (MP), physiotherapy, psychoanalysis, acupuncture, auriculotherapy and laser auriculotherapy (LA), which are potentially beneficial about the painful and emotional aspects in TMD. The goals of this study were evaluate the effectiveness of using LA for pain relief and emotional aspects in TMD and the clinical effects of the association of the therapeutic use of MP with LA. To establish comparison parameters it was used a control group with MP. This study consisted on the participation of 31 volunteers selected from inclusion and exclusion criteria, and divided in three groups: G1 n= 11 - Myorelaxing Plaque, G2 n= 8 - Myorelaxing Plaque and Laser Auriculotherapy, G3 n= 10 - Laser Auriculotherapy. The patients were evaluated in the times T0 (Immediate), T1 (4 weeks) and T2 (8 weeks), according to the criteria and scales of RDCTMD. The results revealed that the laser auriculotherapy has significant effects on the physical and emotional aspects of TMD and that the association of the plaque with the laser auriculotherapy presented the best results on the physical aspects of TMD.